2005
DOI: 10.1016/j.jas.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Implications of burial alterations on luminescence dating of archaeological ceramics

Abstract: Recent mineralogical studies on archaeological pottery samples report significant variations in alkali metal concentrations due to environmental alterations during burial. Here we examine the effects of potassium (K) leaching on luminescence dating. The effect on the estimation of the dose rate is studied by considering four models of leaching (exponential, linear, early and late) and their impact on fineand coarse-grain dating are calculated. The modeling approaches are applied to two cases of pottery in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Severe changes in alkali metals have been correlated with the firing temperature, both in calcareous and non-calcareous pottery. These changes may be manifested either as a loss of alkalis from the sherd or as a concentration gradient between the surface and the core of the sherd (Buxeda i Garrigós, 1999;Buxeda i Garrigós et al, 2001;Picon, 1976;Schwedt et al, 2004Schwedt et al, , 2006Schwedt and Mommsen, 2007;Zacharias et al, 2005). The pattern is attributed to the high mobility of alkalis that are redistributed within the ceramic body upon evaporation of water that forms during thermal dehydroxylation of the clay lattice.…”
Section: Mineralogical Analysismentioning
confidence: 99%
“…Severe changes in alkali metals have been correlated with the firing temperature, both in calcareous and non-calcareous pottery. These changes may be manifested either as a loss of alkalis from the sherd or as a concentration gradient between the surface and the core of the sherd (Buxeda i Garrigós, 1999;Buxeda i Garrigós et al, 2001;Picon, 1976;Schwedt et al, 2004Schwedt et al, , 2006Schwedt and Mommsen, 2007;Zacharias et al, 2005). The pattern is attributed to the high mobility of alkalis that are redistributed within the ceramic body upon evaporation of water that forms during thermal dehydroxylation of the clay lattice.…”
Section: Mineralogical Analysismentioning
confidence: 99%
“…SEM images show signs of high-firing effects, especially for samples D7 and D8. The well-documented effect of cation exchange capacity for high-to over-fired calcareous pottery (Buxeda i Garrigos, 1999;Buxeda i Garrigos et al, 2002;Picon, 1976) has been reported in the literature as being responsible for chemical and mineralogical alterations resulting in a significant K leaching (Zacharias et al, 2005); this effect was also detected in cases of medium of even non-calcareous but high-fired pottery fragments (Zacharias et al, 2006a, Zacharias et al, 2006b, similar Table 2). The vitrification is thus advanced, indicating temperatures of around 850-1050 • C (Maniatis and Tite, 1981).…”
Section: Mineralogymentioning
confidence: 80%
“…In addition, independent PCAs are carried out including either majorminor elements or trace elements. Considering the possibility of some alteration and contamination process (Buxeda i Garrigós, 1999;Zacharias et al, 2005Zacharias et al, , 2007Hong et al, 2011), calcium (Ca) is out of the PCA analysis. Principal component analysis on the data shows that the first two principal components shown in Fig.…”
Section: Data Classificationmentioning
confidence: 99%